Pengaruh media video terhadap pengetahuan dan sikap remaja putri tentang pencegahan stunting di SMA Negeri 1 Labuhan Delikabupaten Deli Serdang - Khairatunnisa Khairatunnisa; Sukamto Sukamto; Andini Mentari Tarigan; Ulan Dari (Journal of Pharmaceutical and Sciences, 2023)
In North Sumatra Province, specifically in the area of Labuhan Deli in Deli Serdang Regency, stunting is still a concern in nutrition among toddlers. In Labuhan Deli, the percentage of instances of stunting rose from 0.48% to 1.46% in 2021. Since adolescent girls will eventually become mothers and bear the next generation, they have a tremendous chance to interrupt the cycle of stunting. Purpose : This study aims to determine the effect of video media on the level of knowledge and attitudes in adolescent girls about stunting prevention at SMA Negeri 1 Labuhan Deli, Deli Serdang Regency.  This is quantitative research with a Quasi Experiment Design. The population of this study was all adolescent girls at the school. The sample of this study was 42 adolescent girls taken by using Proportionate Stratified Random Sampling technique. Data analysis used Paired Sample t-test. The results showed that there were differences in knowledge before (mean = 7.17) and after treatment (mean = 11.00) and there were differences in attitudes before (mean = 28.64) and after treatment with (mean = 39.57). Paired Sample t-test results on the knowledge and attitudes of adolescent girls obtained p value = 0.000 (< α = 0.05). It can be concluded that there was an effect of video media on the level of knowledge and attitudes in adolescent girls about stunting prevention at SMA Negeri 1 Labuhan Deli, Deli Serdang Regency. It is suggested to the local Health Center to be able to utilize video media in the selection of health promotion media.